iological and ecological features fungi of the genus Aspergillus (Eurasian Journal of Ecology, 2019)
The article presents research work on the biological and ecological features fungi of the genusAspergillus, affecting seed crops. Were collected seeds of cereals five district (Talgarsky, Iliisky, Karasai,Zhambulsky, Panfilov) Almaty region. Were discovered these types of fungi: A.flavus, A.tubingensis,A.glaucus, A.niger, A.fumigatus, A.candidus, A.ochraceus.Key words: grains, Aspergillus, identification, morphology, fungicide.